The Efficacy and Safety of Triple vs Dual Combination of Angiotensin II Receptor Blocker and Calcium Channel Blocker and Diuretic: A Systematic Review and Meta‐Analysis. Issue 3 (14th December 2012) - Kizilirmak, Pinar; Uresin, Yagiz; Yildiz, Okan Bulent
Abstract : Many hypertensive patients require ≥2 drugs to achieve blood pressure targets. This study aims to review and analyze the clinical studies conducted with dual or triple combination of angiotensin II receptor blockers (ARBs), calcium channel blockers (CCBs), and diuretics. Medical literature between January 1990 and April 2012 was reviewed systematically and data from eligible studies were abstracted. Data were analyzed using random‐effects models. Of the 224 studies screened, 7563 eligible patients from 11 studies were included. Triple combinations of ARBs (olmesartan or valsartan), CCBs (amlodipine), and diuretics (hydrochlorothiazide) at any dose provided more blood pressure reduction in office and 24‐hour ambulatory measurements than any dual combination of these molecules ( P <.0001 for both). Significantly more patients achieved blood pressure targets with triple combinations (odds ratio, 2.16; P <.0001). Triple combinations did not increase adverse event risk (odds ratio, 0.96; P =.426). Triple combinations at any dose seem to decrease blood pressure more effectively than dual combination of the same molecules without any remarkable risk elevation for adverse events. Further prospective studies evaluating the efficacy and safety of triple combinations, especially in the form of single pills, are required. J Clin Hypertens (Greenwich). 2012;00:00–00. ©2012 Wiley Periodicals, Inc.